Kebebasan Pers dalam Pusaran Demokrasi dan Politik China: Sebuah Systematic Literature Review - Saragih, Safariyarti (Jurnal Pendidikan dan Dakwah, 2025)
Press freedom in modern authoritarian countries, particularly China, faces new pressures due to the integration of traditional political control and digital technology. Automated censorship, artificial intelligence-based propaganda, and regulation of digital platforms limit the plurality of public opinion and direct political narratives. This study uses the Systematic Literature Review (SLR) of international literature 2020–2025 related to press freedom, digital media, propaganda, and authoritarianism. The search was conducted through Scopus, Web of Science, JSTOR, ScienceDirect, Wiley, Sage Journals, and Taylor & Francis, with the selection process following the PRISMA 2020 guidelines. The analysis uses thematic synthesis to map the interaction between state censorship, AI propaganda, self-censorship, and digital public spaces. The results of the study show that China is building  an integrative, adaptive, and predictive digital authoritarian ecosystem. The state not only silences criticism, but also manipulates public opinion through AI-driven propaganda, platform surveillance, and institutional regulation. Self-censorship serves as an effective control mechanism, while citizen resistance emerges in micro and decentralized forms, with limited structural influence. Digital public spaces still exist, but they experience political fragmentation and limited deliberation. These findings confirm that press freedom in China is influenced by digital control and algorithmic governance, not just traditional media. The integration of normative theories of the press, media capture, and digital authoritarianism provides a comprehensive conceptual framework for understanding how modern authoritarian regimes manage information, maintain political legitimacy, and limit public participation. This research makes theoretical and empirical contributions to the study of democracy, political media, and digital authoritarianism.   Kebebasan pers di negara otoriter modern, khususnya China, menghadapi tekanan baru akibat integrasi antara kontrol politik tradisional dan teknologi digital. Sensor otomatis, propaganda berbasis kecerdasan buatan, dan regulasi platform digital membatasi pluralitas opini publik serta mengarahkan narasi politik. Penelitian ini menggunakan Systematic Literature Review (SLR) terhadap literatur internasional 2020–2025 terkait kebebasan pers, media digital, propaganda, dan otoritarianisme. Penelusuran dilakukan melalui Scopus, Web of Science, JSTOR, ScienceDirect, Wiley, Sage Journals, dan Taylor & Francis, dengan proses seleksi mengikuti pedoman PRISMA 2020. Analisis menggunakan thematic synthesis untuk memetakan interaksi antara sensor negara, propaganda AI, self-censorship, dan ruang publik digital. Hasil penelitian menunjukkan bahwa China membangun digital authoritarian ecosystem yang integratif, adaptif, dan prediktif. Negara tidak hanya membungkam kritik, tetapi juga merekayasa opini publik melalui AI-driven propaganda, pengawasan platform, dan regulasi institusional. Self-censorship berperan sebagai mekanisme kontrol yang efektif, sementara resistensi warga muncul dalam bentuk mikro dan terdesentralisasi, dengan pengaruh struktural terbatas. Ruang publik digital tetap eksis, tetapi mengalami fragmentasi politik dan keterbatasan deliberasi. Temuan ini menegaskan bahwa kebebasan pers di China dipengaruhi oleh kontrol digital dan governance algoritmik, bukan hanya media tradisional. Integrasi teori normatif pers, media capture, dan digital authoritarianism menyediakan kerangka konseptual komprehensif untuk memahami bagaimana rezim otoriter modern mengelola informasi, mempertahankan legitimasi politik, dan membatasi partisipasi publik. Penelitian ini memberikan kontribusi teoretis dan empiris bagi studi demokrasi, media politik, dan otoritarianisme digital.